PENELITIAN KECELAKAAN KEHILANGAN PENDINGIN DI KAKI DINGIN REAKTOR PADA UNTAI UJI TERMOHIDROLIKA REAKTOR - Setyaningrum , Winduwati
Loss of coolant accident (LOCA) is the postulated major accident in the safety evaluation of PWR Power Plant. In LOCA, the coolant is flowing out from the cooling system through leaks, may result in the melt of cladding because the reactor core cooling capacity is bad. Six experiments and calculation with computer code of Relap 5 Mod 1 have been carried out for a loss of coolant accident (LOCA) at the Cold Leg in the reactor thermal-hydraulic testing loop facility (RTTLF) of PPTKR-BATAN, namely LKA, LKB, LSA, LSB, LBA, and LBB experiments. LKA and LKB experiments represent Small Break Loca with a leak diameter of 2 mm. LSA and LSB represent Medium Break Loca wit a leak diameter of 5 mm. Large break Loca was carried out using a leak diameter of 10 mm (LBA and LBB). Experiments were carried out with the operation of accumulator safety injection system for LKA, LSA and LBA and the shutdown of the system for LKB, LSB and LBB. All experiments mentioned above were carried out with the operation of High Pressure Safety Injection System (HPIS) and Low Pressure Safety Injection System (LPIS), while make up water kept on being supplied until the experiments were terminated. The phenomena being observed were confined to the effects of the accumulator safety injection toward the reactor safety. The results of experiments were then compared to the results of modeling calculation using computer code of Relap 5 Mod 1. Results of experiments indicate that the pattern of decreasing system pressures (primary loop and pressurizer pressures) for the three types of Loca both in the operation of and shutdown of safety injection system were in general similar. The apparent difference is that after the accumulator was operated, the system pressure at Loca with the operation of accumulator the relatively smaller (nearly flat) decrease in pressure compared to the LOCA with the shutdown of accumulator. Test channel coolant and heating rod temperatures indicate that higher temperature was obtained at LOCA experiment without accumulator compared to LOCA with accumulator because the accumulator=s injection water had participated in the removal of heat from the test channels when the coolant in the test channels was decreasing. At medium and big LOCA, the accumulator safety injection system can rapidly decrease the temperature of both the heating rod and coolant at the test channels as long as the water inventory is available in the accumulator. Afterward, the accumulator is no longer capable of removing it due to the high flow rate of the leaking mass. In this case, further safety measure must be fast carried out (for example by activating the LPIS and continued with long-term cooling) before there is no longer water inventory in the accumulator. For small Loca, the accumulator safety injection system can function longer, hence the temperature of both the heating rod and coolant is relatively controllable. Besides, the time that can be used to anticipate the security and safety of the reactor is longer. In Loca with malfunction accumulator safety injection system, it is apparent that the temperature of both the test channel heating rod and coolant for all types of leak remains relatively high like the initial condition. The results of experiments and calculation are in general similar. Results of calculation of Relap 5 Mod 1 for reactor thermal-hydraulic testing loop facility (RTTLF) tends to show similar phenomena. Although showing in general the similarity of thermal-hydraulic phenomena, the modeling calculation is still needed to obtain more accurate results.